Pertimbangan Hakim Terhadap Permohonan Informasi Publik Kepada Pejabat Pengelola Informasi Publik (Ppid) Pemerintah Daerah (Studi Putusan Nomor : 18/G/KI/2025/PTUN.BL) - Anggalana Anggalana; Erika Armadona (Jurnal Ilmiah Wahana Pendidikan, 2026)
Public information disclosure is an essential principle in ensuring transparent and accountable governance. Law Number 14 of 2008 on Public Information Disclosure guarantees the public’s right to access information and regulates the obligations of public bodies. This study aims to analyze the legal force of the decisions of the Lampung Provincial Information Commission and the legal considerations of judges of the State Administrative Court in Case Number: 18/G/KI/2025/PTUN.BL. This research employs normative legal of research with statutory, conceptual, and case approaches. Data were collected through literature study and interviews. The results indicate that decisions of the Information Commission have binding legal force as long as they are not annulled by a court decision. The Information Commission has exercised its authority in accordance with Law Number 14 of 2008, particularly in applying the consequence test. Furthermore, the judges of the State Administrative Court focused their review on the legality of the Information Commission’s decision and concluded that it was consistent with the law and the principles of good governance.